Synthesis and structural characterization of ferrous trioctahedral smectites: Implications for clay mineral genesis and detectability on Mars. Issue 6 (9th June 2015) - Chemtob, Steven M.; Nickerson, Ryan D.; Morris, Richard V.; Agresti, David G.; Catalano, Jeffrey G.
Abstract Widespread detections of phyllosilicates in Noachian terrains on Mars imply a history of near‐surface fluid‐rock interaction. Ferrous trioctahedral smectites are thermodynamically predicted products of basalt weathering on early Mars, but to date only Fe3+‐bearing dioctahedral smectites have been identified from orbital observations. In general, the physicochemical properties of ferrous smectites are poorly studied because they are susceptible to air oxidation. In this study, eight Fe2+‐bearing smectites were synthesized from Fe2+‐Mg‐Al silicate gels at 200°C under anoxic conditions. Samples were characterized by inductively coupled plasma optical emission spectrometry, powder X‐ray diffraction, Fe K‐edge X‐ray absorption spectroscopy (XAS), Mössbauer spectroscopy, and visible/near‐infrared (VNIR) reflectance spectroscopy. The range of redox states was Fe3+/ΣFe = 0 to 0.06 ± 0.01 as determined by both XAS and, for short integration times, Mössbauer. The smectites have 060 distances (d(060)) between 1.53 and 1.56 Å, indicating a trioctahedral structure. d(060) and XAS‐derived interatomic Fe‐(Fe, Mg, Al) distance scaled with Fe content. Smectite VNIR spectra feature OH/H2O absorption bands at 1.4 and 1.9 µm, (Fe2+, Mg, Al)3‐OH stretching bands near 1.4 µm, and Fe2+Fe2+Fe2+‐OH, MgMgMg‐OH, AlAl(Mg, Fe2+)‐OH, and AlAl‐OH combination bands at 2.36 µm, 2.32 µm 2.25 µm, and 2.20 µm, respectively. The spectra for ferrous saponites are distinct from those for dioctahedral ferric smectites, permitting their differentiation from orbital observations. X‐ray diffraction patterns for synthetic high‐Mg ferrosaponite and high‐Mg ferrian saponite are both consistent with the Sheepbed saponite detected by the chemistry and mineralogy (CheMin) instrument at Gale Crater, Mars, suggesting that anoxic basalt alteration was a viable pathway for clay mineral formation on early Mars.